Synthesis, Structure and Cytotoxicity Testing of Novel 7-(4,5-Dihydro-1H-imidazol-2-yl)-2-aryl-6,7-dihydro-2H-imidazo[2,1-c][1,2,4]triazol-3(5H)-Imine Derivatives - Łukasz Balewski; Franciszek Sączewski; Patrick J. Bednarski; Lisa Wolff; Anna Nadworska; Maria Gdaniec; Anita Kornicka (Molecules, 2020)
The appropriate 1-arylhydrazinecarbonitriles 1a–c are subjected to the reaction with 2-chloro-4,5-dihydro-1H-imidazole (2), yielding 7-(4,5-dihydro-1H-imidazol-2-yl)-2-aryl-6,7-dihydro-2H-imidazo[2,1-c][1,2,4]triazol-3(5H)-imines 3a–c, which are subsequently converted into the corresponding amides 4a–e, 8a–c, sulfonamides 5a–n, 9, ureas 6a–I, and thioureas 7a–d. The structures of the newly prepared derivatives 3a–c, 4a–e, 5a–n, 6a–i, 7a–d, 8a–c, and 9 are confirmed by IR, NMR spectroscopic data, as well as single-crystal X-ray analyses of 5e and 8c. The in vitro cytotoxic potency of these compounds is determined on a panel of human cancer cell lines, and the relationships between structure and antitumor activity are discussed. The most active 4-chloro-N-(2-(4-chlorophenyl)-7-(4,5-dihydro-1H-imidazol-2-yl)-6,7-dihydro-2H-imidazo[2,1-c][1,2,4]triazol-3(5H)-ylidene)benzamide (4e) and N-(7-(4,5-dihydro-1H-imidazol-2-yl)-2-(p-tolyl)-6,7-dihydro-2H-imidazo[2,1-c][1,2,4]triazol-3(5H)-ylidene)-[1,1′-biphenyl]-4-sulfonamide (5l) inhibits the growth of the cervical cancer SISO and bladder cancer RT-112 cell lines with IC50 values in the range of 2.38–3.77 μM. Moreover, N-(7-(4,5-dihydro-1H-imidazol-2-yl)-2-phenyl-6,7-dihydro-2H-imidazo[2,1-c][1,2,4]triazol-3(5H)-ylidene)-4-phenoxybenzenesulfonamide (5m) has the best selectivity towards the SISO cell line and induces apoptosis in this cell line.